Efficacy of dialectical behavior therapy for adolescent self-harm and suicidal ideation: a systematic review and meta-analysis. Issue 7 (20th May 2021) - Kothgassner, Oswald D.; Goreis, Andreas; Robinson, Kealagh; Huscsava, Mercedes M.; Schmahl, Christian; Plener, Paul L.
Abstract: Background: Given the widespread nature and clinical consequences of self-harm and suicidal ideation among adolescents, establishing the efficacy of developmentally appropriate treatments that reduce both self-harm and suicidal ideation in the context of broader adolescent psychopathology is critical. Methods: We conducted a systematic review and meta-analysis of the Dialectical Behaviour Therapy for Adolescents (DBT-A) literature on treating self-injury in adolescents (12–19 years). We searched for eligible trials and treatment evaluations published prior to July 2020 in MEDLINE/PubMed, Scopus, Google Scholar, EMBASE, and the Cochrane Library databases for clinical trials. Twenty-one studies were identified [five randomized-controlled trials (RCTs), three controlled clinical trials (CCTs), and 13 pre-post evaluations]. We extracted data for predefined primary (self-harm, suicidal ideation) and secondary outcomes (borderline personality symptoms; BPD) and calculated treatment effects for RCTs/CCTs and pre-post evaluations. This meta-analysis was pre-registered with OSF: osf.io/v83e7. Results: Overall, the studies comprised 1673 adolescents. Compared to control groups, DBT-A showed small to moderate effects for reducing self-harm ( g = −0.44; 95% CI −0.81 to −0.07) and suicidal ideation ( g = −0.31, 95% CI −0.52 to −0.09). Pre-post evaluations suggested large effects for all outcomes (self-harm: g = −0.98, 95% CI −1.15 to −0.81; suicidal ideation: g = −1.16, 95% CI −1.51 to −0.80; BPD symptoms: g = −0.97, 95% CI −1.31 to −0.63). Conclusions: DBT-A appears to be a valuable treatment in reducing both adolescent self-harm and suicidal ideation. However, evidence that DBT-A reduces BPD symptoms was only found in pre-post evaluations.